مداخل الجودة الشاملة لتأهيل خدمات مؤسسات الاتصال الجزائرية - مؤسسة اتصالات الجزائر أنموذجا - بارك, نعيمة (Université de M'sila, 2018)
All economic Companies seek to find survival, stability and leadership in the market, in defiance of all the rapid changes in the business environment, and rely on many methods, methods and administrative principles. Perhaps the most important of these principles is TQM. This paper aims to highlight the importance of Total Quality Management in the survival of the institution and its continuation in the market. This study also aimed at addressing the rehabilitation of the services of the communication institutions. We took the Algerian Telecom Corporation and the efforts it exerted to reach its goals as a model
Keywords: total quality management , rehabilitation , communication services Companies